Diagnosed Anxiety Disorders and the Risk of Subsequent Anorexia Nervosa: A Danish Population Register Study. (8th September 2015) - Meier, Sandra M.; Bulik, Cynthia M.; Thornton, Laura M.; Mattheisen, Manuel; Mortensen, Preben B.; Petersen, Liselotte
Abstract: Anxiety disorders and anorexia nervosa are frequently acknowledged to be highly comorbid conditions, but still, little is known about the clinical and aetiological cohesion of specific anxiety diagnoses and anorexia nervosa. Using the comprehensive Danish population registers, we aimed to determine the risk of anorexia nervosa in patients with register‐detected severe anxiety disorders. We also explored whether parental psychopathology was associated with offspring's anorexia nervosa. Anxiety disorders increased the risk of subsequent anorexia nervosa, with the highest risk observed in obsessive–compulsive disorder. Especially, male anxiety patients were at an increased risk for anorexia nervosa. Furthermore, an increased risk was observed in offspring of fathers with panic disorder. A diagnosis of an anxiety disorder, specifically obsessive–compulsive disorder, constitutes a risk factor for subsequent diagnosis of anorexia nervosa. These observations support the notion that anxiety disorders and anorexia nervosa share etiological mechanisms and/or that anxiety represents one developmental pathway to anorexia nervosa. Copyright © 2015 John Wiley & Sons, Ltd and Eating Disorders Association.